STRATEGI GAMIFIKASI DALAM MENINGKATKAN LITERASI KEUANGAN SYARIAH GENERASI Z: KAJIAN LITERATUR TERINTEGRASI - Riski Apriliani; Desy Arum Sunarta; Rasyidah Bulqis; Andi Bisyriani (TAKAFUL : Jurnal Ekonomi Dan Perbankan Syariah, 2025)
This study explores the potential of gamification as an adaptive educational strategy to improve Islamic financial literacy among Generation Z learners. Drawing upon key theories from educational psychology, Islamic pedagogy, and digital learning design, this research aims to synthesize conceptual frameworks and empirical findings through an integrative literature review approach. A comprehensive review of forty-three academic sources from 2013 to 2024 was conducted using databases such as Scopus, Web of Science, and ScienceDirect. Thematic coding and comparative analysis were applied to identify core mechanisms of gamification—such as points, badges, leaderboards, and adaptive challenges—and evaluate their alignment with Generation Z’s digital engagement preferences. The findings show that gamification significantly enhances learner motivation, behavioral change, and ethical comprehension when designed with cultural and religious sensitivity. Specific applications in Islamic finance education demonstrate increased retention, improved decision-making, and value alignment. The study concludes that gamified tools, if integrated with Islamic ethics and local wisdom, can bridge the gap between traditional Islamic education and digital learning expectations. These results suggest a new pedagogical direction for educators and policy-makers aiming to cultivate financial literacy in Muslim youth through interactive, ethical, and technology-enhanced learning environments.